E-quadruple flat: Tovey’s Whimsy - Eric Wen (Zeitschrift der Gesellschaft für Musiktheorie)
This paper examines the development section of Beethoven’s Appassionata Sonata in light of Donald Francis Tovey’s whimsical remark about the appearance of an E-quadruple flat. In addition to considering Tovey’s idea, this paper examines the analysis by Heinrich Schenker, and compares the two different analysts’ interpretations. This paper concludes with a renewed examination of the passage leading into the climactic diminished-seventh chord that ends the development section, offering a detailed voice-leading analysis, as well as an idea about its programmatic meaning.